Colonial Mentality and Mental Health Help‐Seeking of Filipino Americans. (9th September 2019) - Tuazon, Victor E.; Gonzalez, Edith; Gutierrez, Daniel; Nelson, Lotes
Abstract : Filipino Americans present with very low rates of mental health help‐seeking. Because of the colonial history between the Philippines and the United States, the authors examined how colonial mentality and internalized oppression, along with ethnic identity, acculturation, and social support, were related to mental health help‐seeking attitudes of Filipino Americans ( N = 410). Furthermore, the authors investigated how colonial mentality affects the ethnic identity of Filipino Americans. Major findings included that colonial mentality was negatively related to ethnic identity development and social support, and higher levels of colonial mentality significantly predicted negative mental health help‐seeking attitudes above and beyond ethnic identity, acculturation, social support, and demographic variables. Implications for the counseling profession are considered.